2008
DOI: 10.1002/cyto.b.20463
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma with flow cytometric evidence of clonal plasmacytic differentiation: A case report

Abstract: Background: Plasmacytic differentiation in mantle cell lymphoma (MCL) occurs rarely. However, no flow cytometric studies that demonstrate plasmacytic (PC) differentiation in MCL have been reported. Herein, we report a case of MCL with PC differentiation identified by flow cytometry.Methods: Morphologic review was performed by hematoxylin and eosin (H&E) stained sections from paraffin-embedded lymph node, colon and bone marrow specimens, and Wright-Geimsa stained bone marrow aspirate smears and touch imprints. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…However, in recent years, several studies have reported occasional tumors with clonally related monotypic plasma cells. [30][31][32]37 These cases are rare but have raised questions on the potential mechanisms Plasmacytic differentiation mantle cell lymphoma involved in their terminal B-cell. This process is normally regulated by the coordinated action of several transcription factors including PAX5, IRF4/ MUM1, BLIMP1, and XBP1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in recent years, several studies have reported occasional tumors with clonally related monotypic plasma cells. [30][31][32]37 These cases are rare but have raised questions on the potential mechanisms Plasmacytic differentiation mantle cell lymphoma involved in their terminal B-cell. This process is normally regulated by the coordinated action of several transcription factors including PAX5, IRF4/ MUM1, BLIMP1, and XBP1.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32]37 Most of these patients had nodal involvement but extranodal dissemination was also frequent. One previous case had a periorbital presentation as one of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these reports, clonally related B cells and fully differentiated plasma cells showing t (11;14) have been found to coexist. [50][51][52] One case showed 3 discernible populations including a B-cell population in transition to plasma cells characterized by coexpression of CD19, CD38, and CD138. 51 These cases may be extremes, but illustrate the ability of MCL cells to differentiate into plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] One case showed 3 discernible populations including a B-cell population in transition to plasma cells characterized by coexpression of CD19, CD38, and CD138. 51 These cases may be extremes, but illustrate the ability of MCL cells to differentiate into plasma cells. The plasmacytic phenotype we describe herein is more subtle but appears to be more common: 3 of 10 primary cases in our study showed CD38 expression of at least twice the median, and in a series of 127 MCL tumors, IRF4 expression has been reported in 35% of cases.…”
Section: Discussionmentioning
confidence: 99%